A Large‐Scale Flexible Plasmonic Nanorod Array with Multifunction of Strong Photoluminescence Emission and Radiation Enhancement. Issue 10 (22nd June 2015) - Li, Jiahua; Wei, Zhiqiang; Xu, Jiuliang; Zhou, Zhang‐Kai; Kong, Delin; Liu, Jingfeng; Liu, Jiaming; Duan, Xiaoyu; Xue, Jiancai; Wang, Jing; Wang, Xuehua
<x xml:space="preserve">Abstract</x> A composite film of gold nanorods and PDMS acts both as an active and passive flexible plasmonic device. Apart from its excellent flexibility, this novel plasmonic nanostructure also exhibits strong multiphoton avalanche photoluminescence, as well as an admirable performance in accelerating the radiation of quantum dots. This multifunctionality makes this film a unique nanomaterial for the construction of future flexible devices.